Research and design for a storage liquid refrigerator considering the characteristics of energy storage batteries - Zhou, Xianwei; Liu, Chuncheng; Qian, Yi; Bi, Zhenyu; Yang, Mo (Frontiers in Energy Research, 2024)
At present, energy storage in industrial and commercial scenarios has problems such as poor protection levels, flexible deployment, and poor battery consistency. Aiming at the pain points in industrial and commercial energy storage application scenarios, this paper comprehensively considers the flexible deployment of the system, the protection level of the cabinet, the structural strength of the cabinet, and the temperature balance characteristics of the battery module in the cabinet, and proposes the solution of the liquid-cooled industrial and commercial energy storage integration cabinet. Improve the reliability and economy of power supply for industrial and commercial users; First of all, the box structure is studied, the box structure is optimized, and based on the liquid cooling technology route, the thermal management scheme of industrial and commercial energy storage integrated cabinet is studied to ensure the consistent temperature between the liquid cooled battery modules and reduce the system capacity loss caused by inconsistent batteries.